2017
DOI: 10.1159/000461596
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous miRNA-146a Enhances the Therapeutic Efficacy of Human Mesenchymal Stem Cells by Increasing Vascular Endothelial Growth Factor Secretion in the Ischemia/Reperfusion-Injured Heart

Abstract: Adult stem cells have been studied as a promising therapeutic modality for the functional restoration of the damaged heart. In the present study, a strategy for enhancing the angiogenic efficacy of human mesenchymal stem cells (hMSCs) using micro-RNA was examined. We investigated whether micro-RNA-146a (miR-146a) influences the secretion of vascular endothelial growth factor (VEGF) and angiogenesis of MSCs. Our data indicated that miR-146a-transfected hMSCs (hMSCmiR-146a) decreased the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…As already mentioned for DNA, the introduction of miRs was reported to modulate the paracrine activity of SCs. For instance, MSCs exhibited a 3-fold enhanced release of VEGF when transfected with miR-146, which in turn led to improved pro-angiogenic effects and cardiac performance after transplantation into rats [501]. A similar high level of VEGF expression was induced by application of miR-126 and miR-377 mimics [502][503][504].…”
Section: Genetic Sc Modificationsmentioning
confidence: 89%
“…As already mentioned for DNA, the introduction of miRs was reported to modulate the paracrine activity of SCs. For instance, MSCs exhibited a 3-fold enhanced release of VEGF when transfected with miR-146, which in turn led to improved pro-angiogenic effects and cardiac performance after transplantation into rats [501]. A similar high level of VEGF expression was induced by application of miR-126 and miR-377 mimics [502][503][504].…”
Section: Genetic Sc Modificationsmentioning
confidence: 89%
“…Another research group also confirmed the antifibrotic effects of miR-29b in angiotensin II induced cardiac fibrosis model [64]. MiR-146a targets VEGF expression and suppresses VEGF dependent proliferation and expansion myofibroblasts [65]. The other miRNAs such as miR-142-3p and miR-433 target high mobility group box 1 (HMGB1), AZIN1, and JNK1, respectively, to ameliorate cardiac fibrosis [66, 67].…”
Section: Mirna and Fibrosismentioning
confidence: 96%
“…miR-126 also contributes to vascular angiogenesis through targeting Cysteine-rich 61 (CCN1) in PTEN/Akt pathway [157]. miR-146a promotes angiogenesis by increasing the expression of VEGF and reducing the fibrotic process at injury site [65]. …”
Section: Mirna and Angiogenesismentioning
confidence: 99%
“…Substantial studies have demonstrated that miRNAs play core roles in the regulation of a variety of cellular processes, including cells growth, cellular apoptosis and fibrosis [5][6][7]. Previously research has suggested miR-155 to be closely associated with cardiovascular heart diseases [8,9].…”
Section: Introductionmentioning
confidence: 99%